India’s Human Development and Social Sector Expenditure. - Pradhan, Rudra Prakash (2007)
This paper examines the trends of India’s human development and social sector expenditure in the globalization regime of the 1990s. The findings imply that the performance of human development is not satisfactory in the country. Given the level of human development that the nation has achieved so far, it has just managed to fall in the group of medium human development. Large-scale regional variations exist across the states. India’s position is also less than satisfactory on the front of social sector expenditure. This was more or less stagnant in the 1990s, and coexists with significant regional variations across the states. The paper finally suggests that India in order to enhance its human development, requires substantial improvement in social sector expenditure.